Red-light activated photoCORMs of Mn(i) species bearing electron deficient 2, 2′-azopyridines. Issue 16 (16th March 2016) - Kottelat, E.; Ruggi, A.; Zobi, F.
Abstract : A family of carbonyl Mn(i ) complexes capable of releasing CO when triggered with red light (≥ 625 nm) is reported. The species are activated by irradiation of their MLCT bands in the 630–690 nm range. Abstract : The realization of CO releasing molecules triggered by light (photoCORMs) within the phototherapeutic window ( λ > 600 nm) constitutes an important goal for potential therapeutic applications of the molecules. The activation of photoCORMs with red/NIR light would enable exploiting the higher depth of penetration of this radiation with respect to higher energy photons. In this article we report a family of carbonyl Mn(i ) complexes capable of releasing CO when triggered with red light (≥625 nm). Such complexes are based on 2, 2′-azopyridine ligands modified by the introduction of electron-donating or electron-withdrawing substituents. Our results indicate that electron deficient ligands induce a gradual decrease of the HOMO−1/LUMO gap of the species ( i.e. of the orbitals involved in the lowest energy transition), thus enabling a fine tuning of their visible absorption maxima between 630 and 693 nm. The synthesis of the complexes and their photodecomposition behaviour towards CO release are described. We suggest that this approach could be generalized for further development of low-energy activated photoCORMs.